Analisis Faktor-Faktor yang Memengaruhi Risiko Likuiditas pada Bank Umum Syariah di Indonesia - Regita Nur Fitriani; Dimas Sumitra Danisworo (Journal of Applied Islamic Economics and Finance, 2020)
This research was conducted to analyze what factors affecting the liquidity risk in Islamic Banks in Indonesia. In this study, the measurement of liquidity risk will be seen from other factors that can affects liquidity risk including Cash Ratio (CsR), Size of Bank (SOB), Third Party Funds (DPK), Capital Adequacy Ratio (CAR), Net Working Capital (NWC), and Investment (INV). The research method used in this research is a quantitative descriptive analysis uses the Eviews 9 program. The object of this analysis is twelve Islamic Banks in Indonesia which have been operating from 2014-2018. The analysis technique used is multiple regression analysis with Random Effect Model (REM) regression model. The results of this study indicate that CsR, SOB, and NWC have a significant effect on liquidity risk. While DPK, CAR, and INV have an insignificant effect on liquidity risk.